Mechanism of Photoredox-Initiated C−C and C−N Bond Formation by Arylation of IPrAu(I)−CF(3) and IPrAu(I)−Succinimide - Kim, Suhong (J Am Chem Soc, 2019)
Herein, we report on the photoredox-initiated gold-mediated C(sp(2))−CF(3) and C(sp(2))−N coupling reactions. By adopting gold as a platform for probing metallaphotoredox catalysis, we demonstrate that cationic gold(III) complexes are the key intermediates of the C−C and C−N coupling reactions. The high-valent gold(III) intermediates are accessed by virtue of photoredox catalysis through a radical chain process. In addition, the bond-forming step of the coupling reactions is the reductive elimination from cationic gold(III) intermediates, which is supported by isolation and crystallographic characterization of key Au(III) intermediates.